Reassessment of mid-Carboniferous glacial extent in southwestern Gondwana (Rio Blanco Basin, Argentina) inferred from paleo-mass transport of diamictites - Gulbranson, Erik L.; Isbell, John L.; Montañez, Isabel P.; Limarino, Carlos Oscar; Marenssi, Sergio Alfredo; Meyer, Kyle; Hull, Clara (Gondwana Research)
Late Paleozoic glacial diamictites occur in many localities in western Argentina, indicating that the region was strongly affected by glaciation during the mid-Carboniferous (late Serpukhovian–early Bashkirian). In most instances these diamictites are found in steeply walled paleovalley settings in the Andean Precordillera. This study presents new data from a locality north of the Precordillera that suggests an additional, distinct, volume of ice existed in the region during the Carboniferous. The glacigenic diamictites in the Rio Blanco Basin were ultimately emplaced as gravity flows, precluding inferences of paleo-ice volume. Fold nose orientation and soft-sediment groove orientations within the diamictites indicate that the deposits were emplaced from north to south, suggesting that glacial ice was most likely not sourced from the proto-Precordillera at this locality, requiring the need for another ice center to the north of the basin. Diamictite facies indicates that the sediment was initially supplied to the study area by a warm-based glacier. Fil: Gulbranson, Erik L. University of California at Davis; Estados Unidos. University of Wisconsin; Estados Unidos Fil: Isbell, John L. University of Wisconsin; Estados Unidos Fil: Montañez, Isabel P. University of California at Davis; Estados Unidos Fil: Limarino, Carlos Oscar. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Geología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Marenssi, Sergio Alfredo. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Geología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Meyer, Kyle. University of California at Davis; Estados Unidos Fil: Hull, Clara. University of California at Davis; Estados Unidos